The interfacial behavior of a thermoelectric thin-film bonded to an orthotropic substrate. (1st April 2023) - Li, Dengke; Chen, Peijian; Huang, Zaixing; Liu, Hao; Chen, Shaohua
Graphical abstract: Highlights: A theoretical model of a thermoelectric film bonded to an orthotropic substrate with or without a bonding layer is proposed. The proposed model functions effectively to analyze the interfacial stress field and stress singularity of the thermoelectric film/orthotropic substrate system. The corresponding interfacial behavior can be improved by tuning geometric and material parameters of the thermoelectric film, and the orthotropic substrate as well as the bonding layer. Abstract: The thermoelectric film/substrate structure has recently drawn great attention due to various applications in fields of sensors in scramjet engines, power generation, refrigeration and reutilization of heat energy, which involves substrates of different properties. In this paper, a theoretical model of a thermoelectric film bonded to an orthotropic substrate with or without a bonding layer is proposed and studied. The interfacial stress field, and the stress intensity factors influenced by various geometric and material parameters of the thermoelectric film and the orthotropic substrate, as well as the bonding layer are comprehensively analyzed. It is found that selecting thermoelectric films with high thermal conductivity and small length facilitates the stability of the thermoelectric film/orthotropic substrate system. The possible damage at the ends of the film/substrate system can be alleviated by tuning effective parameters of the orthotropic substrate. Designing a thick and soft bonding layer can be helpful for the safety of the thermoelectric film/substrate system. The results should be of significant importance for the blooming applications of thermoelectric materials, as well as the design of various film/substrate structures in engineering practice.